Assessment of scintillation proxy maps for a scintillation study during geomagnetically quiet and disturbed conditions over Uganda - Amabayoa, Mirant B; Juruaa, Edward; Cilliersa, Pierre J (International Science Program (ISP) from Uppsala University in Sweden, 2016)
A B S T R A C T The objective of this paper is demonstrate the validity and usefulness of scintillation proxies derived from IGS data, through its comparison with data from dedicated scintillation monitors and its application to GNSS scintillation patterns. The paper presents scintillation patterns developed by using data from the dedicated scintillation monitors of the scintillation network decision aid (SCINDA) network, and proxy maps derived from IGS GPS data for 2011 and 2012 over low latitude stations in Uganda. The amplitude and phase scintillation indices (S4 and σΦ) were obtained from the Novatel GSV4004B ionospheric scintillation and total electron content (TEC) monitor managed by SCINDA at Makerere (0.340N, 32.570E). The corresponding IGS GPS proxy data were obtained from the receivers at Entebbe (0.040N, 32.440E) and Mbarara (0.600S, 30.740E). The derived amplitude (S4p) and phase (sDPR) scintillation proxy maps were compared with maps of S4 and Σφ during geomagnetic storms (moderate and strong) and geomagnetically quiet conditions. The scintillation patterns using S4 and σΦ and their respective proxies revealed similar diurnal and seasonal patterns of strong scintillation occurrence. The peaks of scintillation occurrence with mean values in the range 0.3 < (S4p, sDPR) ≤ 0.6 were observed during nighttime (17:00–22:00 UT) and in the months of March-April and September-October. The results also indicate that high level scintillations occur during geomagnetically disturbed (moderate and strong) and quiet conditions over the Ugandan region. The results show that SCINDAand IGS based scintillation patterns reveal the same nighttime and seasonal occurrence of irregularities over Uganda irrespective of the geomagnetic conditions. Therefore, the amplitude and phase scintillation proxies presented here can be used to fill gaps in low-latitude data where there are no data available from dedicated scintillation receivers, irrespective of the geomagnetic conditions.
Keywords: Low latitude scintillation; Scintillation Proxies; Scintillation Irregularities